Efficient hydrotreated vegetable oil combustion under partially premixed conditions with heavy exhaust gas recirculation. (15th May 2020) - Hunicz, Jacek; Matijošius, Jonas; Rimkus, Alfredas; Kilikevičius, Artūras; Kordos, Paweł; Mikulski, Maciej
Highlights: First in-depth study assessing potential of HVO with partially premixed combustion. Cetane number is key for efficient low temperature combustion with high dilution. HVO allows 43% indicated thermal efficiency with near-Euro VI engine-out emissions. This result is 1.5 percentage points above the optimized diesel operation. Abstract: This study performed a detailed analysis of combustion and emission characteristics of a single-cylinder compression ignition engine fuelled with diesel, hydrogenated vegetable oil (HVO) and their blend (50/50). Taking advantage of the high reactivity of HVO, the aim was to investigate how changes in fuel injection and exhaust gas recirculation (EGR) strategies can achieve partially premixed combustion with superior efficiency and ultra-low engine-out emissions. Without EGR, and with a multi-pulse injection strategy optimized for diesel, combustion timings were the same for all three investigated fuels. HVO exhibited higher tolerance to EGR in terms of combustion retarding, so it was possible to use high recirculation rates. This reduced nitrogen oxides, while maintaining high indicated efficiency. The pilot injection control allowed further extending the EGR dilution limit without incurring trade-offs with combustion efficiency and related carbon monoxide and unburned hydrocarbon emissions. Additionally, heavy EGR conditions supported reduction of soot for all three tested fuels. However, the best trade-off between soot and other emission compounds was observed for HVO. HVO also resulted in the lowest emissions of aldehydes and aromatics. In conclusion, on the given engine platform at a steady-state, mid-load operating point, HVO allowed for 43% indicated thermal efficiency with engine-out nitrogen oxides and carbon monoxide emissions near to Euro VI limits. This efficiency level was 1.5 percentage points above that for the optimized diesel operation.